2010
DOI: 10.1287/moor.1090.0428
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Location Guide for the Unsure: Approximation Algorithms for Min-Max Location Problems

Abstract: This paper studies an extension of the k-median problem under uncertain demand. We are given an n-vertex metric space V d and m client sets. The goal is to open a set of k facilities F such that the worst-case connection cost over all the client sets is minimized, i.e., minThis is a "min-max" or "robust" version of the k-median problem. Note that in contrast to the recent papers on robust and stochastic problems, we have only one stage of decision-making where we select a set of k facilities to open. Once a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Another interesting consequence of Theorem 12 is for the robust k-median problem [1]. Here we are given a metric…”
Section: Hardness For Robust K-medianmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting consequence of Theorem 12 is for the robust k-median problem [1]. Here we are given a metric…”
Section: Hardness For Robust K-medianmentioning
confidence: 99%
“…Anthony et al [1] gave an O(log m+log k)-approximation algorithm for robust k-median, and showed that it is hard to approximate better than factor two. At first sight this problem may seem unrelated to crossing matroid basis.…”
Section: Hardness For Robust K-medianmentioning
confidence: 99%
See 1 more Smart Citation
“…A key property shared by these hierarchies is that they are locally integral; that is, the q-th relaxation in the hierarchy coincides exactly with the convex hull of feasible 0-1 solutions, when both are projected onto any q-dimensional subspace corresponding to q variables in the program. 2 Specifically for Sherali-Adams, the q-th relaxation for a given 0-1 linear program with variables x 1 , . .…”
Section: Lp Hierarchies and Faithful Roundingmentioning
confidence: 99%
“…We prove that certain types of "faithful" approximation algorithms for a variant of DkS which we call SMALLEST m-EDGE SUBGRAPH (or SmES) imply approximation algorithms for LD2S, and then show how to construct such an algorithm for SmES; combining these two together yields our improved approximation for LD2S. We seem to be the first to formally define and study SmES, although it has been used in previous work (sometimes implicitly) as the natural minimization version of DkS, see e.g. [35], [25], [2]. In SmES we are given a graph G and a value m, and want to find the subgraph of G with at least m edges that has the fewest vertices.…”
Section: Introductionmentioning
confidence: 99%